Plagiochasma intermedium Lindenb. & Gottsche (Aytoniaceae, Marchantiophyta), the third species of Plagiochasma for southern South America - Flores, Jorge Rafael (2015)
Plagiochasma Lehm. & Lindenb. is a widely distributed genus mainly in semi-arid areas. Two species were formerly recognized for southern South America, P. ruprestre (G. Forst.) Steph. and P. argentinicum Bischl. In the present contribution, we give account for the presence of P. intermedium Lindenb. & Gottsche in Southern South America, extending the previously known distribution range in a large extent. In order to distinguish P. intermedium from the remaining species of South America, a key is elaborated. Photomicrography and a distribution map of P. intermedium are also presented.